Fresno County Bar Association Luncheon: State Bar President David Heilbron Speaker - Watkins, Howard::::::::: (1986)
Fresno County Bar Association President Judy Soley, Fresno County Bar Association President-elect Howard Watkins, State Bar Board Public Member Glee Ewell, District 5 Governor Dennis Cornell and David Heilbron